Butylamine functionalized graphene oxide: experimental and DFT studies on the corrosion inhibition efficiency of the MgAZ13 alloy in a 3.5% NaCl environment. Issue 4 (26th January 2023) - Palaniappan, N.; Cole, Ivan; Kuznetsov, A.; Caballero-Briones, F.; Manickam, Sivakumar
Abstract : Figure A depicts the electrostatic energy in edge functional groups with non-bonding electrons and suggests an interaction with the metal surface. Figure B shows protonated electrostatic energy that indicates the donation of a pair of electrons to the metal surface. Abstract : A unique property of graphene oxide (GO)-based functionalized materials is their corrosion retardation. We have designed a butylamine functionalized GO material as a corrosion-resistant coating for magnesium alloys in a 3.5% NaCl environment. The functionalized materials were characterized by different spectroscopic techniques: Raman, FESEM (field emission scanning electron microscopy), TEM (transmission electron microscopy), XRD (X-ray powder diffraction), and FTIR (Fourier transform infrared spectroscopy). The electrochemical properties were evaluated by various electrochemical methods such as CV (cyclic voltammetry) and LSV (linear sweep voltammetry). The redox properties of the composite materials showed excellent electrochemical stability up to an applied voltage of 600 mV. The corrosion inhibition efficiency was obtained to be around 69%. The DFT (density functional theory) results support the experimental findings.